Neuroprotective potential of ferulic acid against cyclophosphamide‐induced neuroinflammation and behavioral changes. Issue 12 (27th September 2022) - Mishra, Tejesvi; Nagarajan, Kandasamy; Dixit, Praveen Kumar; Kumar, Vinay
Abstract: In the present study, ferulic acid (FRA) has been explored for possible neuroprotective effects against cyclophosphamide (CP)‐induced neurotoxicity in the Swiss Albino mice. Animals were divided into five groups and treated with FRA for fourteen days and a single dose of CP was administered on the seventh day. Animals were subjected to neurobehavioral tests such as the forced swim test and Morris Water Maze test. On day fifteenth, the brain was removed and used for biochemical analysis. The outcome of the study showed that CP administration induced significant neurotoxicity in the form of depression, anxiety, and cognitive dysfunction. Cyclophosphamide administration also reduced the activity of antioxidant enzymes, reduced the level of neurotransmitters (i.e., dopamine, 5‐HT, and BDNF), anti‐inflammatory cytokines (IL‐10), and increased lipid peroxidation and proinflammatory cytokines (IL‐1β, IL‐6, and TNF‐α). Additionally, CP administration increased the level of acetylcholine esterase. Treatment with FRA significantly reversed these behavioral, and biochemical markers towards normal and mitigated CP‐induced neurotoxic manifestation. Practical applications: Ferulic acid has a variety of pharmacological activities viz. anti‐inflammatory, antioxidant, antimicrobial activity, anti‐cancer, and anti‐diabetic effects. The results of the present study showed that FRA mitigates the neurotoxicity (i.e., alteration of neurotransmitters, inflammation, and oxidative stress) induced by CP in mice. Treatment with FRA knowingly overturned the behavioral and biochemical markers in the direction of the moderated CP‐influenced neurotoxic demonstration. Thus, FRA can be useful in the prevention of anticancer drugs induced neurotoxicity. Contrariwise, supplementary in‐depth studies are obligatory to bring FRA from bench to bedside that it be used as an adjuvant among chemotherapeutically treated patients. Abstract : Treatment and outcome paradigm.